Distributions of Rare Earch Element (REE) in Mangrove Surface Sediment by Nuclear Technique - Kumar, Krishnan; Elias, Saion (INTI International University, 2022)
The Juru rivers are highly industrial, urbanized and agricultural. The aim of the study was to examine the geochemical bases and enrichment of rare earth elements in Juru mangrove sediments. This study is carried out to investigate the concentrations of rare earth element (REEs) elements Samarium (Sm), Europium (Eu), Yttrium (Yb), Lutetium (Lu), and Terbium (Tb) present in surface mangrove sediments of Juru River, West Coast of Peninsular Malaysia. The concentrations of rare earth elements in the sediments were determined by using the instrumental neutron activation analysis (INAA) method. For calibration and quality control procedures, standard reference material SL-1 and blank samples were irradiated together with sediment samples. The degree of anthropogenic impact on sediments were computed using enrichment factor. The concentration and enrichment factor of all the REE elements ranged between 0.42 mg/kg (Lu), 7.55 mg/kg (Sm), 0.77 (Lu) and 2.96 (Tb), respectively. The geochemical behavior of REEs in surface sediments and normalized patterns (chondrite and shale) have been studied. These findings indicate that the level of pollution has not reached an extreme or severe level, but ongoing studies should be carried out on the inputs of anthropogenic activities at Juru river.